TEACHING JAPANESE TEA CEREMONY TO CHINESE UNIVERSITY STUDENTS: DEVELOPING ENGLISH LEARNING MATERIALS : Received: 25th January 2024 Revised: 21st February 2024, 27th February 2024, 29th February 2024 Accepted: 25th January 2024 - Carreira, Junko Matsuzaki; Shioda , Naoko (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study is a preliminary study for creating teaching materials for the development of global human resources who can communicate their own (Japanese) culture, such as the tea ceremony, to the world in English. This study aims to clarify what foreigners are interested in, what they find important, and what they would like to know more about the tea ceremony to create teaching materials reflecting foreigners’ interests and concerns. The results indicated that the participating students enjoyed hands-on activities, such as actually preparing and drinking tea and learning how to eat wagashi (traditional Japanese sweets), even in an online environment. Furthermore, some students demonstrated interest not only in hands-on experiences but also in the history of the tea ceremony, distinctions between Japanese and Chinese tea cultures, and various aspects of the tea ceremony, including tea, tea utensils, traditional clothing (kimono), and the differences among tea ceremony schools. Based on these findings, it is recommended to create educational materials for Japanese university students learning the tea ceremony in English that cover not only the fundamental etiquette of the tea ceremony, but also provide comprehensive knowledge about the broader aspects of the tea ceremony.